Anthropometry and physical characteristics of middle weight female weightlifters - Cheng, Z.; Bai, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction This paper describes the results of research aimed at comparing the anthropometry and physical characteristics of female weightlifters and female college students of the same age. Methods Morphological and functional tests were conducted on each subject under the same circumstances and standard and work related indices and anthropometric and physical data were statistically analyzed. Results / Discussion In terms of body proportions, when compared with average female college students, female weightlifters have shorter lower limbs, lower indexes of lower limbs/height and upper limbs/height, higher indexes of sitting vertex height/height and Achilles`s tendon/height. There is no significant difference in the height of the two groups. Female weightlifters have larger limb circumferences and wider shoulder breadth, suggesting training adaptations and increased muscle strength. Female weightlifters have higher BMI and WHR values, but there is no difference in vital capacity. This suggests the need to pay more attention to the study of female weightlifters` cardio-pulmonary function and their health condition.